Optimizing the Production of High-Quality Silage from Jingkenuo 2000 Fresh Waxy Maize: The Synergistic Effects of Microbial Fertilizer and Fermentation Agents - Min Hou; Yang Li; Fan Yang; Weidong Cui; Xinxin Huang; Deli Dong; Lifeng Dong; Bo Zhang (Fermentation)
Probiotics improve the quality of silage during the planting and fermentation processes. This study was designed to investigate the accumulation of nutritional components in the fresh corn variety Jingkenuo 2000 waxy maize under different fertilization conditions and its effectiveness as silage feed. The nutrient accumulation trends of dry matter (DM), starch, neutral detergent fiber (NDF), acid detergent fiber (ADF), crude protein (CP), and ether extract (EE) in the stems, leaves, grains, and whole plant of Jingkenuo 2000 waxy maize were evaluated during different growth cycles. The relative feed value (RFV) was also assessed, with the results showing that the whole plant of Jingkenuo 2000 waxy maize at the wax stage was most suitable for use as silage. The experiment conducted in the present study was carried out in a completely random block design with two additives and three fertilizer application conditions: no-additive + conventional fertilization treatment (CKCK); no-additive + conventional fertilization + drip irrigation of bacterial solution treatment (CKJJ); no-additive + conventional fertilization + microbial organic fertilizer treatment (CKYJ); additive + conventional fertilization treatment (FJCK); additive + conventional fertilization + drip irrigation of bacterial solution treatment (FJJJ); and additive + conventional fertilization + microbial organic fertilizer treatment (YJFJ). Additionally, the nutrient composition, fermentation quality, and bacterial community structure of the silage fermentation treatments were analyzed. The results indicate that there was significant interaction between the additive and fertilization treatments, with them significantly influencing the parameters CP, EE, NDF, ADF, and RFV (p < 0.01). In particular, the treatment combining additives, conventional fertilization, and drip irrigation of bacterial solution exhibited the highest CP, EE, and starch (p < 0.01) among all the tested treatments, while also displaying the lowest NDF and ADF contents (p < 0.01). Furthermore, this treatment reduced the pH value (p < 0.01), decreased bacterial diversity, and fostered the growth of Lactobacillus. Overall, the findings presented herein demonstrate that, through precise nutritional accumulation monitoring and scientific biological pretreatment methods, Jingkenuo 2000 waxy maize has the potential to become a high-quality silage feed.